Transparent dielectric TiO2/SiO2 coatings for thermal shielding and self-cleaning applications - Venkatesh Yepuri; R S Dubey (Kuwait Journal of Science)
Economical fabrication of one-dimensional dielectric reflectors using the hybrid sol-gel spin coating process is significant compared to sophisticated chemical and physical vapor deposition techniques. In this work, we preferred the TiO2 and SiO2 materials to fabricate dielectric reflectors due to their high refractive index contrast and easy tailor-ability of the reflectance window in the spectral region of interest. Here, we fabricated the near-infrared reflectors composed of TiO2/SiO2 films with a minimum number of stacks to attain the constructive interference of incident light so that maximum reflectance can be assured in the specific spectral region. X-ray diffraction (XRD) studies of the monolayer TiO2 and SiO2 confirmed the existence of anatase-TiO2 and amorphous-SiO2 phases, respectively. The TiO2 and SiO2 films were found to have refractive indices of 2.6 and 1.5, respectively, as measured by spectroscopic ellipsometry.The field-emission scanning electron microscopy (FESEM) analysis evidenced the fabrication of 2.5 stacks of TiO2/SiO2 films (TiO2/SiO2)2.5. The reflectance measurement revealed 100 percent reflection in the near-infrared region having its center wavelength of 833 nm. In addition, we have examined the water contact angle of the reflector ( 2.5 stacks) using the sessile drop technique and found its contact angle of 29.3O, which suggests its anti-fogging and self-cleaning applications.